Three new for the fauna of West Kazakhstan species of the orders Mantodea, Orthoptera and Embioptera - Temreshev, Izbasar I. (Acta Biologica Sibirica, 2023)
Three species of orthopteroid insects (Insecta, Polyneoptera) are recorded from West Kazakhstan for the first time. The Asian giant mantes Hierodula tenuidentata Saussure, 1869 (Mantodea) and the Turkistan webspinner Embia tartara Saussure, 1896 (Embioptera) are found in Mangystau oblast. It is possible that this species was able to spread north due to climate warming. The ant-loving cricket Myrmecophilus acervorum (Panzer, 1799) (Orthoptera) is recorded from Atyrau oblast. Probably both species were imported in this region with planting material. Moreover, the order Embioptera and families Myrmecophilidae and Embiidae are recorded from West Kazakhstan for the first time.